Evidence for a preformed transducer complex organized by the B cell antigen receptor. - Wienands, J (1996)
The B cell antigen receptor (BCR) consists of the membrane-bound immunoglobulin (mIg) molecule and the Ig-alpha/Ig-beta heterodimer, which functions as signaling subunit of the receptor. Stimulation of the BCR activates protein tyrosine kinases (PTKs) that phosphorylate a number of substrate proteins, including the Ig-alpha/Ig-beta heterodimer of the BCR itself. How the PTKs become activated after BCR engagement is not known at present. Here, we show that BCR-negative J558L cells treated with the protein tyrosine phosphatase inhibitor pervanadate/H2O2 display only a weak substrate phosphorylation. However, in BCR-positive transfectants of J558L, treatment with pervanadate/H2O2 induces a strong phosphorylation of several substrate proteins. Treatment with pervanadate/H2O2 does not result in receptor crosslinking, yet the pattern of protein phosphorylation is similar to that observed after BCR stimulation by antigen. The response requires cellular integrity because tyrosine phosphorylation of most substrates is not visible in cell lysates. Cells that express a BCR containing an Ig-alpha subunit with a mutated immunoreceptor tyrosine-based activation motif display a delayed response. The data suggest that, once expressed on the surface, the BCR organizes protein tyrosine phosphatases, PTKs, and their substrates into a transducer complex that can be activated by pervanadate/H202 in the absence of BCR crosslinking. Assembly of this preformed complex seems to be a prerequisite for BCR-mediated signal transduction.